2006
DOI: 10.1111/j.1399-3054.2006.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of plant cell activities by polypeptides secreted by Eutypa lata, a vineyard fungal pathogen

Abstract: Eutypa dieback is a devastating disease induced in vineyards by the fungal pathogen Eutypa lata. The fungus colonizes the xylem tissues of trunk and cordons but is never found in the annual canes. Nevertheless, dwarfed shoots and leaf necrosis observed in diseased plants indicate that a necrotic signal can spread at a distance from the infected area. Eutypine, a small cyclic molecule, and related compounds have been postulated as the toxins inducing these symptoms. In this work, we evidence that E. lata secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…The toxicity of the high molecular weight hydrophilic compounds produced by several fungi, identified as exopolysaccharides, has been reviewed by Evidente and Motta (2001). Indeed, work on eutypa dieback disease has shown that polypeptides secreted by E. lata participated in cell structure damage in grapevine (Octave et al 2006). The toxic effect of the same type of compound secreted by Pal and Pch has been shown in the case of esca disease on grapevine (Luini et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of the high molecular weight hydrophilic compounds produced by several fungi, identified as exopolysaccharides, has been reviewed by Evidente and Motta (2001). Indeed, work on eutypa dieback disease has shown that polypeptides secreted by E. lata participated in cell structure damage in grapevine (Octave et al 2006). The toxic effect of the same type of compound secreted by Pal and Pch has been shown in the case of esca disease on grapevine (Luini et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are involved in cell structure damage and affect grapevine metabolism (Octave et al 2006b and. In addition, the toxicity of proteins secreted by Pa. chlamydospora (Pch) and Pm.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies have been raised against E. lata ascospores and hyphal material and used to identify the fungus by immunodiffusion and immunofluorescence (Francki & Carter, ). More recently, it has been shown that E. lata secretes various polypeptides (Octave et al ., ,b) and enzymes (Schmidt et al ., ) into its culture medium. Rabbit antibodies raised against these polypeptides were used to develop a sensitive and specific serological assay for the in planta identification of E .…”
Section: Discussionmentioning
confidence: 99%